RILM in context - Mackenzie, Barbara Dobs; Melo, James G. (Música em Contexto, 2008)
Searching for information today is a significantly different activity than it was a decade ago, even more so than four decades ago when RILM (Répertoire International de Littérature Musicale), an abstracted bibliographic guide to writings about music, was founded. This article reviews its development in Brazil.